Formulation and Evaluation of Herbal Hair Shampoo, Mask and Serum (International Journal of Scientific Research in Science and Technology, 2025)
A vital component of the body is hair. It is a measure of health. A hair mask can help keep our hair hydrated. They are particularly helpful for damaged or dry hair. A hair mask, hair shampoo could make our hair stronger. The most vital organ in the mammalian system, the hair follicle determines appearance, distinguishes gender, protects against extreme heat, and aids in self-defence. Younger generations have started to face significant challenges with hair loss as a result of numerous lifestyle-related changes, including exhaustion, worry, junk food consumption, and the use of various hairstyling colouring techniques. The natural ingredients in the herbs provide the body with nutrients and other beneficial minerals without having any negative effects. Chrysanthemum flowers are used for the preparation of hair conditioning agents. Because chrysanthemum flowers have so many health advantages for the scalp and hair, they make excellent hair masks, shampoos, and serums. They contain vitamins and minerals; chrysanthemum blossoms can be used as a natural conditioner to treat dandruff and even encourage hair development. chrysanthemum flowers provide a number of advantages that immediately enhance the health, look, and feel of hair, we utilize them in hair treatments, shampoos, and serums. Chrysanthemum’s antibacterial and anti-inflammatory qualities help to reduce dandruff and soothe irritated scalps. By reducing inflammation, irritation, and dryness or flakiness, it helps keep the scalp healthy when added to shampoos or serums. Chrysanthemum is a natural component that is generally mild and appropriate for a range of hair types, including those with sensitive scalps. It is a safe option for those who have allergies or who prefer natural alternatives because it is less likely to irritate skin or trigger allergic reactions. Hair shampoos, hair masks and hair serum are common herbal hair care products.